A Case of Antibiotic-Induced Posterior Reversible Encephalopathy Syndrome. (October 2020) - Gilbert, Brian Wesley; Gabriel, Ali; Velazquez, Laura
Purpose: To report a case of posterior reversible encephalopathy syndrome (PRES) in a 75 year-old patient who was taking concomitant ciprofloxacin and metronidazole.Method: Case reportResults: A patient had been prescribed ciprofloxacin and metronidazole during a recent hospitalization and continued this regimen outpatient. Two weeks after discharge and 3 weeks after initiation of her regimen, she was brought to the emergency department after developing acute weakness and lightheadedness. After admission, the patient declined more rapidly and began seizing with subsequent intubation. Initial computed tomographic (CT) imaging showed no acute neurological abnormalities, and a sepsis workup was initiated. After negative CT, a magnetic resonance imaging scan was performed that showed a T2 flair and hyperdensity consistent with PRES. The final diagnosis was considered to be PRES secondary to ciprofloxacin/metronidazole utilization.Conclusion: Antibiotic induced PRES is a condition that needs to be explored more thoroughly.